The National Trade Facilitation Roadmap for Exports Enhancement and Diversification of the Republic of Tajikistan 2019 – 2024 - United Nations Economic Commission for Europe (United Nations, 2020)
This National Trade Facilitation Roadmap for Exports Enhancement and Diversification provides the framework for a national trade facilitation reform programme over a five-year period (2019-2024) and includes a strategic vision supported by goals and activities, and performance indicators to measure progress against set targets. It is the result of a consultative effort of the National Coordination Committee on Trade Facilitation (CCTF), under the UNECE guidance, and in collaboration with key international partners including the ITC and UNCTAD. This document has been developed in the context of the project on “Removing regulatory and procedural barriers to trade in the Republic of Tajikistan” at the request of the Government.